Sinonasal papillomas: A single centre experience on 137 cases with emphasis on malignant transformation and EGFR/KRAS status in “carcinoma ex papilloma” - Maisch, Saskia; Müller, Sarina Katrin; Traxdorf, Maximilian; Weyerer, Veronika; Stoehr, Robert; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
Among the three major histological subtypes of sinonasal papillomas, inverted (ISP) and oncocytic (OSP) sinonasal papillomas tend to undergo malignant transformation to carcinoma. However, criteria determining risk of recurrence and malignant progression have not been established. Recently, EGFR and KRAS mutations were detected to be characteristic for ISP and OSP, respectively. In this study, we analyzed 137 sinonasal papilloma cases (132 ISP and 5 OSP) for clinicopathological characteristics, frequency of recurrences/malignant transformation, and histological types and genetic features of carcinoma ex Schneiderian papilloma. OSP presented at a higher age than ISP (median, 75 vs. 57 years) and affected predominantly females. Overall frequency of recurrences and malignant transformation was 23.1% and 9.5%, respectively. Rates of recurrence (33.3% vs. 22.0%) and malignant transformation (33.3% vs. 8.8%) were higher in OSP compared to ISP, respectively. Carcinomas (n = 10) occurred mostly synchronously, more frequently in females and mainly associated with ISP (n = 9). Squamous cell carcinoma (SCC) was the most frequently associated malignancy. Concordant EGFR (in ISP/associated carcinoma) and KRAS (in the OSP/associated carcinoma) mutations were detected in all successfully analyzed matching papilloma/carcinoma pairs, confirming their shared clonal origin. Results of this large study are in line with recent studies showing frequent EGFR and KRAS mutations in sinonasal carcinoma ex Schneiderian papilloma. As the papilloma component might on occasion be missed on biopsy of synchronous carcinoma ex papilloma, EGFR and KRAS mutation testing represents a promising molecular surrogate for sinonasal “carcinoma ex papilloma”, at the same time offering an opportunity for targeting mutant EGFR in this rare cancer type.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Carcinoma ex papilloma; EGFR; Inverted papilloma; KRAS; Oncocytic papilloma; Schneiderian papilloma; Sinonasal papilloma; Squamous cell carcinoma